Antibacterial dialdehyde sodium alginate/ε-polylysine microspheres for fruit preservation. (1st September 2022) - Ge, Liming; Li, Zijing; Han, Miao; Wang, Yongjie; Li, Xinying; Mu, Changdao; Li, Defu
Graphical abstract: Highlights: DSA-PL conjugates were obtained by Schiff's base reaction between PL and DSA. Spherical DSA-PL MPs show good dispersity and acid-sensitive degradation property. DSA-PL MPs possess effective and broad-spectrum antibacterial activity. DSA-PL MPs have potential application as antibacterial agents for fruit preservation. Abstract: Food security is an important global public health issue, which will not only endanger consumers' life and health, but also cause serious food waste. Herein, antibacterial dialdehyde sodium alginate/ ε -polylysine microspheres (DSA-PL MPs) were developed to effectively prolong the shelf life of fruit. DSA was prepared by periodate oxidation of sodium alginate. Then the PL was conjugated onto DSA backbone via the Schiff's base reaction to synthesize DSA-PL conjugates, followed by the emulsification and Ca 2+ ions crosslinking to obtain DSA-PL MPs. The results indicate that DSA-PL MPs show smooth spherical particle, relatively narrow size distribution and good dispersity. In vitro degradation rate of DSA-PL MPs is higher in acetate buffer (pH = 5.0) than that in PBS buffer (pH = 7.4), showing acid-sensitive degradation property. Significantly, DSA-PL MPs possess strong broad-spectrum antibacterial activity, which can effectively extend the shelf life of fruit. Overall, DSA-PL MPs possess promising application as antibacterial agents for fruit preservation.